Charles J. Adams Antara Reduksionisme dan Anti-Reduksionisme dalam Kajian Agama - Riyadi, Abdul Kadir (Program Pascasarjana UIN Sunan Ampel Surabaya, 2010)
This paper is about a critical survey of Charles J. Adamsâ insights concerning the definition and nature of religion. We are particularly interested in digging up the logic and methodological inconsistency of Charles Adams as far as his offer on religious studies is concerned. Initially we were impressed by the power of his allusions. But the deeper we go the more we found out that his thought is replete with methodological incongruence. First, he is not certain about the definition of religion; an uncertainty that leads to a lot of fundamental errors in the description of religion as a whole. Second, he is not sure what line of argument he follows, the fact that leads to confusion whether he is reductionist or anti-reductionist. It is about this confusion that this paper is concerned with. Although a major part of this paper deals with religions in general, its theme and problems are of particular importance to the study of Islam.